(untitled) - O'Connor, Michael Patrick; (1950-2007) (U.S.A, 1980)
In this extensive and eclectic reconsideration of classical Hebrew poetics, O$1 (BConnor evaluates the assumptions that have guided scholars for more than two hundred years. The result is (3z(Ba great leap forward in the analysis and interpretation of early Hebrew poetry.(3ys
Keywords: Hebrew poetry, Biblical -- History and criticism